2013
DOI: 10.1177/1474474012469004
|View full text |Cite
|
Sign up to set email alerts
|

Performing a more-than-human material imagination during fieldwork: muddy boots, diarizing and putting vitalism on video

Abstract: Sarah Whatmore has argued that ' [t]here is an urgent need to supplement the familiar repertoire of humanist methods that rely on generating talk and text with experimental practices that amplify other sensory, bodily and affective registers and extend the company and modality of what constitutes a research subject'. But how does one do this? What kinds of research practices are useful? And more specifically, what kinds of methods can help to conjure and enact a vitalist materialism in the field? This essay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 9 publications
(12 reference statements)
0
15
0
1
Order By: Relevance
“…This enabled an understanding of the role the works came to play while in situ, and to see the reactions they instilled: whether it was a desire to come closer, the need to tell a friend or to simply ignore it. Like Richardson‐Ngwenya (), I found that the methods I employed were thus not post‐human as such, but instead encouraged me to adopt an attitude that attended to the vital material relations that surrounded me, and indeed others.…”
Section: Knitting the City: Guerrilla Methodsmentioning
confidence: 92%
“…This enabled an understanding of the role the works came to play while in situ, and to see the reactions they instilled: whether it was a desire to come closer, the need to tell a friend or to simply ignore it. Like Richardson‐Ngwenya (), I found that the methods I employed were thus not post‐human as such, but instead encouraged me to adopt an attitude that attended to the vital material relations that surrounded me, and indeed others.…”
Section: Knitting the City: Guerrilla Methodsmentioning
confidence: 92%
“…For instance, 'reintroducing dynamic perspectives and contours into the landscape, as well as texture and feeling, perception and imagination, so elegantly traced by topologies, with something added' [35], and a new vitalist 'material imagination' reimagine both human and 'non-human materialities as animated by dynamic and lively capacities to affect change and to participate in political life' [36]. Thus, the hybrid configuration perspective of non-representative theory may help people to understand how people make knowledge of the world, how they physically and socially make the world through the ways they move and mobilize people, objects, information and ideas [37].…”
Section: Hybrid Geographiesmentioning
confidence: 99%
“…Geography has a long tradition of critical reflection on and experimentation with the spaces through which research is practised (DeLyser & Starrs, ; Driver, ; Katz, ). A leitmotif of these disciplinary discussions has been the centrality of “the field” to geographical knowledge production, and indeed the methodological stakes of recent post‐humanist and related modes of theorising have largely been framed in terms of how they might reorient us to the question of what composes this field as well as transform the very performance of fieldwork itself (Daniels et al., ; Dewsbury & Naylor, ; Richardson‐Ngwenya, ; Whatmore, ). In comparison, there has been much less attention afforded to how these contemporary theories might inform spaces of pedagogy and research training, except in relation to the geographical field as a crucial site for applying or grounding the concepts and approaches learned in lectures (Bassett, ; Latham & McCormack, ; Lorimer, ).…”
Section: Post‐humanist Research and The Geographical Workhopmentioning
confidence: 99%